An Increasing Sweet Corn Production With Hybrid Compost - Iwan Hasrizart (Jurnal Scientia, 2024)
This research aims to determine the response of giving vegetable compost and cow urine to the growth and production of sweet corn (Zea mays L). This research was conducted on Jalan Kelambir V, Hamparan Perak District, Deli Serdang Regency. The research method used was a factorial Randomized Group Design (RAK) with 2 treatments. The first treatment is vegetable compost (K) consisting of 4 levels of enrichment, namely K0= 0 kg/ plot, K1= 1 kg/ plot, K2= 2 kg/ plot, K3= 3 kg/ plot. And the second treatment, namely cow urine (U), consists of 4 treatment levels, namely U0= 0 liter/plot, U1= 1 liter/plot, U2= 2 liters/plot, U3 = 3 liters/plot. The parameters observed were stem diameter (mm), leaf area (cm), fruit length per sample (g), production per sample (g), and production per plot (g). The results of the treatment of giving vegetable compost fertilizer had no significant effect on the parameters, namely stem diameter (mm), leaf area (cm), production per sample (g), and production per plot (g), but had a significant effect on fruit length per sample (g). Meanwhile, cow urine had no significant effect on stem (mm), leaf area (cm), fruit length per sample (g), production per sample (g), and production per plot (g). The interaction between the application of vegetable compost fertilizer and cow urine had no significant effect on stem (mm), leaf area (cm), fruit length per sample (g), production per sample (g), and production per plot (g).